Case series of physical examinations on psychiatric inpatients: Influence of a structured form on the quality of documentation. (2013) - Murray, Jonathan; Baillon, Sarah
Abstract : Background: There is a strong association between mental disorder and poor physical health. However, research indicates that the standard of physical examinations performed on psychiatric inpatients is not good. Aims: This study aimed to assess the completeness of the physical examinations performed by psychiatric trainees on an acute psychiatric inpatient unit. Method: A retrospective analysis of 236 sets of inpatient case notes was performed. The quality of the documentation was assessed using a 50-point scoring system based on the presence or absence of reference to various items of examination. Results: Eighty-five percent of the patients received a complete examination and 13% were not examined at all. The mean points score was only 20 out of 50, indicating that the overall standard of documentation was quite low. However, when a proforma was used rather than free text documentation, significantly more information was recorded. Conclusions: Most psychiatric patients are not receiving a thorough physical examination. An essential first step to address the problem would be to divide physical examinations into three categories according to the psychiatric setting and reach a consensus on a gold standard for each type. Standards could also be improved by the more widespread use of a well-designed proforma and greater supervision of psychiatric trainees' performance in this area.